Performance of cervical cytology and HPV testing for primary cervical cancer screening in Latin America: an analysis within the ESTAMPA study (2023)
ABSTRACT: Background: Cervical cytology remains widely used as the initial tool in cervical cancer screening worldwide. WHO guidelines recommend replacing cytology with primary HPV testing to reach cervical cancer elimination goals. We assessed the performance of cytology and high-risk HPV testing to detect cervical precancer, cervical intraepithelial neoplasia (CIN) grade 3 or worse (CIN3+) among women aged 30-64 years participating in the ESTAMPA study. Methods: Women were screened with cytology and HPV across ESTAMPA study centres in Latin America. Screen-positives were referred to colposcopy with biopsy collection and treatment as needed. Those with no evident precancer were recalled at 18-months for a second HPV test to complete disease ascertainment. Performance indicators for cytology and HPV to detect CIN3+ were estimated. Findings: 30,606 participants with available cytology and HPV results were included in the analysis. A total of 440 histologically confirmed CIN3s and 30 cancers were diagnosed. Cytology sensitivity for CIN3+ was 48.5% (95% CI: 44.0-53.0), whereas HPV testing had a sensitivity of 98.1% (95% CI: 96.3-96.7). Specificity was 96.5% (95% CI: 96.3-96.7) using cytology and 88.7% (95% CI: 88.3-89.0) with HPV. Performance estimates varied substantially by study centre for cytology (ranging from 32.1% to 87.5% for sensitivity and from 89.2% to 99.5% for specificity) while for HPV results were more consistent across sites (96.7%-100% and 83.6-90.8%, respectively). Interpretation: The limited and highly variable sensitivity of cytology strongly supports transition to the more robust and reproducible HPV-based cervical screening to ensure progress towards global cervical cancer elimination targets in Latin America. Funding: IARC/WHO, UNDP, HRP/WHO, NCI and local funders.